Efficacy of attractive targeted sugar bait stations against malaria in Western Province Zambia: epidemiological findings from a two-arm cluster randomized phase III trial - Ruth A. Ashton; Kochelani Saili; Chama Chishya; Handrinah Banda Yikona; Annie Arnzen; Erica Orange; Chanda Chitoshi; John Chulu; Titus Tobolo; Frank Ndalama; Irene Kyomuhangi; Willy Ngulube; et al. (Malaria Journal)
Abstract Background Attractive targeted sugar bait (ATSB) stations containing bait (to attract) and ingestion toxicant (to kill) sugar-foraging mosquitoes are hypothesized to reduce malaria transmission by shortening the lifespan of Anopheles vectors. Methods A two-arm cluster-randomized controlled trial (cRCT) was conducted in Western Province Zambia. Seventy clusters of 250–350 households were assigned (1:1) by restricted randomization to an intervention arm (ATSB) or control arm (no ATSB) in the context of standard of care vector control (insecticide-treated nets and/or indoor residual spraying). Two ATSB stations (Westham Sarabi, 0.11% dinotefuran w/w) were maintained on exterior walls of eligible household structures for a 7-month deployment period (December-June) during the high malaria transmission season. The primary outcome was clinical malaria incidence among two consecutive seasonal cohorts of children aged 1–14 years, followed-up monthly from January-June in 2022 and 2023. Secondary outcome was Plasmodium falciparum prevalence among individuals aged over six months. Analysis compared clinical malaria incidence and prevalence between arms among the intention-to-treat population. Results ATSB coverage, assessed by cross-sectional survey, was 98.3% in March–April 2022 and 89.5% in March–April 2023. 4494 children contributed any follow-up time to the cohort, with 2313 incident malaria cases in the intervention arm (1.28 per child per six-month transmission season), and 2449 in the control arm (1.38 per child-season). The incidence rate ratio between the two arms was 0.91 (95% CI 0.72–1.15, p = 0.42). 2536 individuals participated in cross-sectional surveys, with prevalence of P. falciparum 50.7% in the intervention arm and 53.5% in the control arm. The odds ratio between the two arms was 0.89 (95% CI 0.66–1.18, p = 0.42). Secondary covariable-adjusted and subgroup analyses did not substantially alter the findings. No serious adverse events associated with the intervention were reported. Conclusions Two ATSB stations deployed per eligible structure for two consecutive transmission seasons did not result in a statistically significant reduction in clinical malaria incidence among children aged 1–14 years or in P. falciparum prevalence in rural western Zambia. Further studies are needed to assess the efficacy of ATSB stations in different settings and with different deployment strategies. Trial registration The trial is registered with Clinicaltrials.gov (NCT04800055).